Retinal nerve fiber layer thickness in children: the Gobi desert children eye study - Wang, Chun-Yan; Jonas, Jost B. (Investigative ophthalmology & visual science, 2018)
Purpose: Because there is a paucity of population-based data on retinal nerve fiber layer thickness (RNFLT) for children, we measured the RNFLT and its associations in schoolchildren. - Methods: The population-based Gobi Desert Children Eye Study included all schoolchildren aged 6 to 21 years living in Ejina, Inner Mongolia. The children underwent a comprehensive ocular examination with cycloplegic refractometry and spectral-domain optical coherence tomography of the optic nerve head. The peripapillary RNFLT was measured on the optical coherence tomography images of a circular scan with a diameter of 3.4 mm. - Results: Out of 1565 participants, RNFLT data were available for 1440 (92.5%) children. The mean global RNFLT was 101.3 ± 9.2 μm in right eyes. The RNFLT was thickest in the temporal inferior sector (157.3 μm), followed by the temporal superior sector (143.8 μm), the nasal inferior sector (109.7 μm), the nasal superior sector (106.9 μm), temporal sector (85.2 μm), and the nasal sector (61.7 μm). In multivariate analysis, the RNFLT decreased with higher myopic refractive error (P < 0.001), male sex (P = 0.001), higher intraocular pressure (P = 0.002), and lower birth weight (P = 0.03). It was not significantly associated with age (P = 0.19), body mass index (P = 0.57), mean arterial blood pressure (P = 0.33), pulse rate (P = 0.28), and subfoveal choroidal thickness (P = 0.11). - Conclusions: The RNFLT in children showed a regional distribution, with the thickest part in the temporal inferior sector and the thinnest part located in the nasal sector. The overall RNLFT significantly decreased with higher myopic refractive error and male sex. In schoolchildren, in contrast to adults, the RNFLT did not decrease with older age. These findings may be considered when interpreting RNFLT data in children.
Gesehen am 06.05.2019